PENGARUH PENDEKATAN JELAJAH ALAM SEKITAR (JAS) PADA MATERI GELOMBANG TRANSVERSAL TERHADAP HASIL BELAJAR PESERTA DIDIK - Poli, Delivia Natalia; Marianus; Rampengan, Alfrie M.; Rende, Jeane C.; Tumimomor, Farly R.; Tiwow, Vistarani A. (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
The natural exploration approach (JAS) is used to utilize the surrounding natural environment as an object of knowledge. The purpose of this study was to determine the effect of the JAS approach on wave material on student learning outcomes. This study used a quasi-experimental method with a nonequivalent control group design. The results showed that the experimental class produced an average pretest score of 6.14, and after learning using the natural exploration approach (JAS), the average posttest score was 63.66. The control class had an average pretest score of 4.42 and an average posttest score of 40. A statistical analysis using an independent sample t-test obtained a significance value (2-tailed) of 0.001 <0.05, thus rejecting and accepting . Based on the results, it can be stated that the use of the natural exploration approach (JAS) has an effect on student learning outcomes.